(untitled) (The Research of Medical Science Review, 2025)
Background: Existing literature shows conflicting results on the relationship between serum calcium levels and pregnancy-induced hypertension (PIH), with some studies suggesting lower calcium levels contribute to PIH, while others do not establish a clear link. This controversy prompted the planning of this study to clarify these inconsistencies and enhance understanding. Objective: To compare Duration: Six months w.e.f. 02-04-2024 to 01-10-2024. Methodology: This case-control study was conducted at Ghurki Trust Teaching Hospital, Lahore, with 60 patients. After obtaining informed consent, participants' demographics, blood pressure, and serum calcium levels were recorded. Based on blood pressure measurements, participants were classified into two groups: those with pregnancy-induced hypertension (PIH) and normotensive women. Data were analyzed using SPSS, and statistical tests compared serum calcium levels between the groups, with a significance level set at p ≤0.05. Results: The study included 60 participants, with a mean age of 32.15 ± 6.03 years, and a mean gestational age of 30.45 ± 3.26 weeks. Most participants were overweight (70%) and primiparous (46.7%). Pregnancy-induced hypertension (PIH) was observed in 33.3% of participants. Significant differences were found in blood pressure, with higher systolic and diastolic pressures in the PIH group. Serum calcium levels were significantly lower in the PIH group (8.05 ± 0.42 mg/dl) compared to controls (9.73 ± 1.27 mg/dl). Conclusion: Pregnancy induced hypertension was observed in 33.3% of participants, and serum calcium levels were significantly lower in the PIH group compared to the controls. This difference was consistent across subgroups based on age, gestational age, BMI, and parity.